Exploration of anti EFG1 locked nucleic acid gapmers to control Candida albicans filamentation. Issue 12 (17th December 2021) - Araújo, Daniela; Mil-Homens, Dalila; Jørgensen, Per Trolle; Fialho, Arsénio M.; Wengel, Jesper; Henriques, Mariana; Silva, Sónia
Abstract : Introduction: Antisense oligonucleotides (ASOs) have been successfully utilized to silence gene expression for the treatment of many genetic human diseases, and particularly the locked nucleic acid (LNA) chemical modification is extensively used with this propose. However, LNA-modified ASOs have never been exploited for controlling virulence genes of Candida . EFG1is an important determinant of virulence that is involved in the switch from yeast to filamentous forms in C. albicans . Thus, our main goal was to explore LNA antisense gapmers for controlling EFG1gene expression and to block C. albicans filamentation. Methods: A set of five LNA-modified gapmers were designed with different chemical modifications (phosphorothioate backbone (PS) and/or palmitoyl-2'-amino-LNA) and ASO length. The in vitro performance of the different ASOs was evaluatedon their ability to control EFG1 gene expression, by qRT-PCR, and to reduce C. albicans ' filamentation, through filaments' enumeration by microscopy. The in vivo therapeutic potential of ASOs was assessed using a G. mellonella model of infection, through a survival assay. Results: In vitro results showed that all ASOs were able to reduce the levels of EFG1gene expression, consequently reducing the levels of C. albicans filamentation around 50%. Interestingly, in vivo tests showed that the LNA-modified gapmer with PS backbone and palmitoyl-2'-amino-LNA was more effective at preventing G. mellonella infections. Conclusions: Undeniably, this work promotes the development of a novel approach for the treatment of Candida infections based on the delivery of ASOs coupled with LNA chemical modification.